High freqency hearing loss in percusion players - ROGOWSKI, P.; RAKOWSKI, A.; JAROSZEWSKI, A. (Archives of Acoustics, 1999)
In a number of reports it has been observed that a prolonged exposure to music at sound pressure levels exceeding 100 dB leads to substantial temporary threshold shifts TTS2, reaching 60-80 dB in the range of high frequencies. Cumulative effects of such exposures result in acoustic trauma, affecting the perception of pitch, loudness and time, accompanying the decrease of hearing sensitivity. The hearing threshold in percussion players is affected largely at high frequencies, where substantial decrease of sensitivity between 10 and 16 kHz reaching 40 to 75 dB has been observed. In the present report a number of hearing thresholds in percussion players and in control group consisting of musicians who have never played percussion instruments or were long exposed to their sounds have been analysed with reference to thein- exposure characteristics.